Schemes for acceleration a part of electrons of drive electron bunches in the dielectric wakefield structure - Linnik, A.F.; Krivonosov, G.A.; Omelayenko, O.L.; Sotnikov, G.V. (Problems of Atomic Science and Technology, 2023)
The paper presents several schemes for obtaining the main (witness) bunches from a long sequence of electron bunches, as well as from a part of a single electron bunch in the dielectric wakefield structure. The selected part of the electron bunches passes into the accelerating phase of the wake field due to the difference in the geometric path length between the separated electrons and the excited wakefield.